XAVIER FOLEY (DOUBLE BASS) KELLYYU-CHIEH LIN (PIANO). - HOLLINGSWORTH, LEAH (Strad, 2021)
The article offers information on the musical performance performed by the musicians including Xavier Foley and Kelly Yu-Chieh Lin at Shriver Hall Concert Series in Baltimore, Maryland on March 6, 2021.